KEPRIBADIAN GURU MATEMATIKA YANG ISLAMI - Maulidah Lailiyah (TADRIS: Jurnal Pendidikan Islam, 2018)
AbstractTeacher is one of profession that is recommended by Islam because teacher’s duty are so precious. In Islam, the teacher not only do the learning, but also lead and give the students  a direction to the right way. As well as mathematic teacher who are not only assigned to deliver materials or mathematic lesson, but also should be able to guide the students in order to be always on the way that Allah blesses, and also be a good model for students. But the reality, some mathematic teachers have not been able to do the job professionally according to the shari’a. They only carry out the duty because of financial demands. Therefore a strong religious foundation, a large Islamic knowledge, and a qualified teacher’s personality competence are needed in order to carry out the task well.Key words: teacher; Islamic; personality